Impulsividade na Coreia de Sydenham: estudo cognitivo e comportamental - Hugo Almeida Chaves de Resende (2021)
INTRODUCTION: Sydenham's Chorea (SC) is a neuropsychiatric syndrome characterized by motor, behavioural and cognitive symptoms, mediated by antibodies produced against Group A Beta Haemolytic Streptococcal cell’s wall (GABHS). These antibodies cross-react with basal ganglia antigens, resulting in neurological dysfunctions. Cognitive-behavioural manifestations in SC have been studied to improve the patient’s clinical approach and to better understand the cortical-striatal connections. In this study, inhibitory control, impulsivity and the ability to recognize facial emotions were tested in participants with SC. OBJECTIVES: To investigate cognitive and behavioural aspects of impulsivity in a cohort of patients with SC. Further, to evaluate the performance of these participants in an emotion recognition test. PATIENTS AND METHODS: Twenty-five patients with SC underwent neurological examination and neuropsychological tests to assess inhibitory control, impulsivity and the ability to recognize emotions. The results were compared to those of 27 healthy participants, matched for age, education and sex. RESULTS: The SC group showed higher scores on the motor items of the UFMG Sydenham's Chorea Rating Scale (USCRS) (p=0.001). By the cognitive assessment, this same group exhibited worse results than the control, also statistically significant, by the mini mental state exam (p=0.009), by the frontal assessment battery (FAB) (p=0.026), by the FAB motor items (p=0.028), by the “F” fluency test (p=0.012), by the Digit Span test (p=0.01) and the direct order Digit Span (p=0.002). There was also a different performance in the Hayling test, Part B: quantitative score (p=0.004), error(s) (p=0.006), qualitative score (p=0.002). Additional difference was noted at the 5-digit test: error reading (s) (p=0.032) and choice time (p=0.005), choice error(s) (p=0.007), choice corrections (p=0.049), inhibition (p=0.045) and flexibility (p=0.019), with worse performance by the SC group. This group also presented worse results at the nine-hole peg test with the right hand (p=0.032), which correlated with the motor USCRS (p=0.010). Another correlation (Spearman's) observed was between the “S” fluency test and the motor USCRS (p=0.019). The scores at the facial emotion recognition test were similar between the groups. The behavioural assessment showed a discrepant result, with statistical significance: the control group had a higher score at the Attentional BIS (p=0.003). Correlations were observed between the Stroop and 5-digits tests with impulsivity. In the first case, the correlation was observed between the section Colour – Time and Delay Discounting Test (DDT) (p=0.033), Colour – Total Errors and DDT (p=0.049), Words – Time and motor BIS (p= 0.016). In the second, between error counting and motor BIS (p=0.012) and between shifting time and motor BIS, shifting corrections with planning BIS and total BIS. CONCLUSIONS: Participants with SC showed more inhibitory control failures than controls. The non indicative BIS of impulsive behaviour and the Hayling Test favorable to the presence of impulsivity in the SC group shows us a behavioural-cognitive dissociation, which is supposedly due to the different neural bases of each of these aspects. SC can be listed among the diseases that involve the basal ganglia and manifest as movement disorders, cognitive and behavioural changes.